Estudio definitivo minicentral hidro eléctrica Shitariyacu Pachiza – Huicungo - Flores Flores, Juan José Segundo (1999)
The privileged geographical location of the Peru makes hydraulic energy certainly represents the major source of energy in the country, despite the fact that to date only a very small part of the exploitable potential is used and only about 44% of the population has electricity. Of the 8000 5 MW calculated as economically usable throughout the country, only 2250 MW are subject to current use (1). It should be noted that the production of electrical energy through hydropower is cheaper compared with the energy produced by thermal power plants and other sources. The development of our peoples is linked to a large extent with the power at a constant and permanent manner, because this is a netesidad the construction of hydroelectric power stations, which are the only ones that will give us an energy secured 24 hours a day. We know also that in this area the Costa and Sierra regions are benefit most great works, qu...